Sistem Pendukung Keputusan Penentuan Kualitas Kayu untuk Kerajinan Mebel menggunakan Metode Electre Studi Kasus PT. Asia Mujur - Andre Adrian; Rusmin Saragih; Magdalena Simanjuntak (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Wood is the main element that determines the quality of a furniture product or other wooden crafts. Furniture was originally a wood carving craft industry, so that the furniture products produced emphasize the artistic aspect (carvings). The lack of knowledge of furniture companies and laypeople in this industry results in difficulties in determining the decision to choose wood to be used as a material for good and quality furniture crafts. Determining the quality of wood for furniture crafts needs to be strengthened by the increasing needs of the furniture industry. This industry has a high demand for quality wood raw materials to produce durable and aesthetic furniture products. Therefore, determining the quality of wood is crucial in ensuring the success of production and customer satisfaction..